5x+6=4(x-2)

Simple and best practice solution for 5x+6=4(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6=4(x-2) equation:


Simplifying
5x + 6 = 4(x + -2)

Reorder the terms:
6 + 5x = 4(x + -2)

Reorder the terms:
6 + 5x = 4(-2 + x)
6 + 5x = (-2 * 4 + x * 4)
6 + 5x = (-8 + 4x)

Solving
6 + 5x = -8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6 + 5x + -4x = -8 + 4x + -4x

Combine like terms: 5x + -4x = 1x
6 + 1x = -8 + 4x + -4x

Combine like terms: 4x + -4x = 0
6 + 1x = -8 + 0
6 + 1x = -8

Add '-6' to each side of the equation.
6 + -6 + 1x = -8 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = -8 + -6
1x = -8 + -6

Combine like terms: -8 + -6 = -14
1x = -14

Divide each side by '1'.
x = -14

Simplifying
x = -14

See similar equations:

| 7(e-8)=98 | | 3(x+7)+6(2x+3)=69 | | 4v-2=5v-6 | | 3x-7x=37 | | 2y-12=12-2p | | 2u=12 | | 2x^4+16x^3+32x^3=0 | | x^2-8x-14=0 | | x^3+8x+14=0 | | (w+3)7=-7 | | 0=x^2-14x+49 | | 13=m | | 3(x-2)=12x | | 9y-8-5y=5y-5 | | [3t-2]+6=2 | | -9+5x+2=48 | | 1.5t=-9 | | 8=12y+6x | | .6w=.48 | | 4(m+6)=4 | | 3x-12+3=33 | | 63=9m | | 2h+4h-9h=h | | a-11=-18 | | 10x-4x-2-1=15 | | 4[1-(-6x-2)]=120x+44 | | 4[1-(6x-2)]=120x+44 | | 5x-(2x-1)=10+2(3-x) | | 3x^2-5=34 | | -.4=g-4.9 | | -5x-6+9x=34 | | 2x^2+3+5x=0 |

Equations solver categories